ANALISIS PENGARUH FINANCING TO DEPOSIT RATIO (FDR)TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Suryani, Suryani (IAIN Walisongo Semarang, 2011)
AbstractThis study aimed to (1) analyze the condition of Financing to Deposit Ratio (FDR) ofIslamic Banking in Indonesia, (2) analyze the profitability of sharia banking inIndonesia; and (3) to analyze the influence of Financing to Deposit Ratio (FDR) of theprofitability of sharia banking in Indonesia. This study took samples at Islamic banksin Indonesia including 11 Islamic Banks (BUS), 23 Business Units of Sharia Banking(UUS). The research data is from Islamic Banking Statistics published by BankIndonesia from January 2008 until December 2010 (Financial Ratio Study to BUSand UUS period 2008-2010). The number of Islamic banks used is 34 banks. Thetechnique uses simple linear regression analysis with the help of the programEVIEWS version 5.***Kajian ini bertujuan untuk: (1) menganalisis kondisi Financing to Deposit Ratio(FDR) pada Perbankan Syariah di Indonesia, (2) menganalisis profitabilitasperbankan syariah di Indonesia (3) menganalisis pengaruh Financing to DepositRatio (FDR) profitabilitas perbankan syariah di Indonesia. Sampel dari kajian inimeliputi 11 bank syariah (BUS), 23 Unit Usaha Syariah (UUS). Data peneitian inidiperoleh dari Statistik Perbankan Syariah yang diterbitkan oleh Bank Indonesiadari bulan Januari 2008 hingga Desembar 2010 (Kajian mengenai Financial RatioBUS dan UUS dalam periode 2008-2010) Sebanyak 34 bank dilibatkan dalampenelitian ini. Adapun teknik yang digunakan dalam kajian ini adalah analisisregresi linear dengan bantuan program EVIEWS versi 5.Keywords: profitabilitas, Return on Asset (ROA), Financing to DepositRatio (FDR), statistik perbankan syariah, perbankan syariahIndonesia